Metode Pembelajaran Menghafal Juz 'amma di Pondok Pesantren Darussalam Dukuhwaluh Purwokerto - Nurkholis Kurniawan; Nawawi Nawawi (Institut Agama Islam Negeri Purwokerto, 2021)
The method is one of the most influential aspects to achieve something success in carrying out the teaching and learning process. In the educational process of memorizing Juz' amma a teacher is programmed in an instructional design to make students or students learn actively which emphasizes the provision of learning resources. So in essence the educational procedure for memorizing juz' amma is a path or method carried out in the educational process in order to facilitate educational activities in memorizing the last juz' amma or juz in the Qur'an at the Darussalam Islamic Boarding School Dukuhwaluh Purwokerto. This research aims to identify what and how the educational process and also the procedures used in memorizing Juz' amma at Pondok Pesantren Darussalam Dukuhwaluh Purwokerto. This type of research is field research with descriptive qualitative research type. To get the data needed. The results of the research show that the Juz Amma memorization education procedure at the Darussalam Islamic Boarding School Dukuhwaluh Purwokerto is implemented and various methods of memorization education are applied. There are also memorization education methods used at the Darussalam Islamic Boarding School Dukuhwaluh Purwokerto, namely the wahdah procedure, namely memorizing verse per verse, the khitabah or writing method, the observing or Sima'i method, the jama method, the repeat method with fellow students and the deposit method. Keywords: Learning Method of Memorizing Juz Amma